Cardioprotection and Thyroid Hormones in the Clinical Setting of Heart Failure - Mastorci, Francesca; Sabatino, Laura; Vassalle, Cristina; Pingitore, Alessandro (Frontiers in Endocrinology, 2020)
Cardioprotection, including methods and mechanisms that lead to the reduction in infarct size, is considered an important target of new therapeutic strategies in the evolution of post-ischaemic heart failure (HF). This is a growing research field since ischemic heart disease is the main cause of morbidity and mortality worldwide. Cardioprotection is a dynamic process characterized by a number of factors that need to be considered: 1) mechanisms leading to myocardial damage; 2) activation of the various protective factors, including cellular signaling pathways; 3) involvement of the cellular and extracellular districts. This generates a complex and intertwisted network of cooperating units, whose result is independent of the function of the units in the absence of cooperation. In this scenario, heart and thyroid (TH) liaison adds complexity as arises from the numerous TH effects on the heart. They starts from the genomic mechanisms, including cardiac differentiation during perinatal period, in which THs cause transcriptional programming leading to the typical gene expression profile of the adult heart, and non-genomic action addressed to the maintenance of cardiovascular homeostasis. Nowadays, recent results highlights multiple actions of the TH system on the heart that can have a relevant role in cardioprotection, such as the regulation of oxidative stress status, different intracellular pro-survival pathways, the preservation of mitochondrial function and morphology, the antifibrotic and proangiogenic effect, and also the potential induction of cell regeneration and growth. This opens to new perspectives on physiological and therapeutic effects of TH and their involvement into cardiac regeneration/reparative process and cardiac remodelling. This review is focused on the actions of thyroid hormones, and in particular triiodothyronine, on the heart, as a cardioprotective therapeutic agent-highlighting cellular up to clinical evidences.